1991
DOI: 10.1002/j.2161-0045.1991.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between College Women's Occupational Interests and a Single‐Sex Environment

Abstract: This study investigated whether the gender composition of the home and high‐school environment in which a woman was reared has an influence upon her occupational interests. Results indicated that college women who reported attending a single‐sex high school and who also had brothers demonstrated interest in non‐traditional careers significantly more often than did their counterparts who attended coed schools. Those women from single‐sex high schools reporting having sisters only did not differ significantly fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…For example, Gilroy and her colleagues (Rubenfeld & Gilroy, 1991;Scheye & Gilroy, 1994) examined differences in occupational interest for females who had attended co-ed versus all-girl high schools. They found that females who had brothers at home and who had attended all-girl high schools were Educational Research and Evaluation 539 more likely to be interested in math-and science-related careers than females who had only sisters or who had attended co-ed high schools (Rubenfeld & Gilroy, 1991). Although the current study did control for levels of parental education and parental expectations (although it was only measured with a single item, which may have reduced its ability to show differences), other home socializing factors might be important for understanding female math trajectories.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…For example, Gilroy and her colleagues (Rubenfeld & Gilroy, 1991;Scheye & Gilroy, 1994) examined differences in occupational interest for females who had attended co-ed versus all-girl high schools. They found that females who had brothers at home and who had attended all-girl high schools were Educational Research and Evaluation 539 more likely to be interested in math-and science-related careers than females who had only sisters or who had attended co-ed high schools (Rubenfeld & Gilroy, 1991). Although the current study did control for levels of parental education and parental expectations (although it was only measured with a single item, which may have reduced its ability to show differences), other home socializing factors might be important for understanding female math trajectories.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…When counseling diverse populations, career counselors should explore the relationship between image norms and other individual difference variables, including gender (Piel Cook, 1993, disability status (Friehe, Aune, & Leuenberger, 1996), sexual orientation (Pope et al, 2004), ethnic identity (Fouad & Arbona, 1994;Perrone, Sedlacek, & Alexander, 2001), age (Brewington & Nassar-McMillan, 2000), and social economic status (Trusty & Ng, 2000). Counselors should address the needs of both male and female clients who expect to choose nontraditional careers (Rubenfeld & Gilroy, 1991), because image norms typically reflect gender-traditional occupations.…”
Section: Career Development Professionalsmentioning
confidence: 99%
“…Astin (1977Astin ( , 1993, after controlling for a variety of background characteristics, including socioeconomic status (parental education and income) and institutional selectivity, found that women's colleges still had positive effects on overall academic development, cultural awareness, writing skills, critical thinking ability, and foreign-language skills. Much of the recent literature has examined the difference in cognitive outcomes between students attending women's colleges and those attending coeducational colleges (Lee and Bryk, 1986;Ossana, Helmes, and Leonard, 1992;Rubenfeld and Gilroy, 1991). Smith and her colleagues (1995) found that women's colleges have a direct, positive effect on women's academic involvement.…”
Section: Studying Women's Collegesmentioning
confidence: 99%